Oxidation behaviour of a next generation polycrystalline Mn containing Ni-based superalloy - Pedrazzini, S; Child, D; West, G; Doak, S; Hardy, M; Moody, M; Bagot, P (Elsevier, 2015)
A prototype next-generation superalloy containing 1 at.% Mn was oxidised in air at 800 °C for 100 h, and compared with a commercial Ni-based superalloy. The oxide scale consisted of a multi-phase layered structure measured by Atom Probe Tomography as uppermost NiCr2Mn2O4, followed by an inhomogeneous mix of Cr2O3, spinel MnCr2O4 and rutile (Ti,Cr)O2. The Mn did not form a homogeneous, surface passivating oxide layer. Despite this, the alloy showed a 3 × reduction of oxide thickness compared to a commercial polycrystalline Ni-based superalloy.